2013
DOI: 10.1111/exd.12236
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin retinol acyltransferase as a potential prognostic marker for malignant melanoma

Abstract: Metabolism inside cells differs between cancer and normal cells. Because disturbance of vitamin A metabolism might be important, we investigated expression of the enzymes lecithin retinol acyltransferase (LRAT) and RPE65 by immunohistochemistry in melanoma metastases and melanocytic nevi. Semiquantitative evaluation of this expression revealed downregulated expression of RPE65 in malignant melanoma compared with benign melanocytic nevi (P < 0.001). In contrast, expression of LRAT was not significantly differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Interestingly, patients with LRAT hypermethylation did present a favorable prognosis (p = 0.03). Consistent with our finding, a recent study has also demonstrated high expression of LRAT in melanoma metastases was inversely correlated with patient survival [12]. Our data suggest that the frequent LRAT hypermethylation may represent a useful predictor to stratify CRC.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, patients with LRAT hypermethylation did present a favorable prognosis (p = 0.03). Consistent with our finding, a recent study has also demonstrated high expression of LRAT in melanoma metastases was inversely correlated with patient survival [12]. Our data suggest that the frequent LRAT hypermethylation may represent a useful predictor to stratify CRC.…”
Section: Resultssupporting
confidence: 92%
“…The drop in LRAT expression is also consistent with previous findings of reduced retinyl esters with UVA and UVB exposure and reduced LRAT expression and activity in SCC . It has been argued that a decrease in retinyl esters may contribute to retinoid deficiency in cancer cells, and LRAT expression may reduce cancer cell survival . But by also showing that RA synthesis enzymes and binding proteins are increased we paint a different picture.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, lecithin retinol acyltransferase (LRAT) is a major enzyme involved in vitamin A metabolism by catalysing the esterification of all-trans-retinol into all-trans-retinyl ester, which regulates various physiological processes. However, it is frequently inhibited by promoter hypermethylation in numerous cancers 40 41 42 . In this study, we showed that the LRAT promoter (GRCh37/Hg19 chr4: 155663541–155664999) was hypermethylated in six IUGR placental shares and the inter-group comparisons displayed a similar result ( Fig.…”
Section: Resultsmentioning
confidence: 99%